Correction's method of the electron density model in ionosphere by ray tracing techniques. Issue 6 (15th March 2015) - Settimi, Alessandro; Pezzopane, Michael; Pietrella, Marco; Scotto, Carlo; Bianchi, Silvio; Baskaradas, James A.
Highlights Defining a correction procedure to obtain a reliable group delay of the ray path. An analytical relation between the electron content and the group delay is discussed. An oblique radio link can be improved by varying the electron density grid. A right correction can be provided by linearly re-distributing the electron content profile.